2019
DOI: 10.1101/744136
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Essential omega-3 fatty acids tune microglial phagocytosis of synaptic elements in the developing brain

Abstract: Omega-3 fatty acids (n-3 polyunsaturated fatty acids; n-3 PUFAs) are essential for the functional maturation of the brain. Westernization of dietary habits in both developed and developing countries is accompanied by a progressive reduction in dietary intake of n-3PUFAs. Low maternal intake of n-3 PUFAs has been linked to neurodevelopmental diseases in epidemiological studies, but the mechanisms by which a n-3 PUFA dietary imbalance affects CNS development are poorly understood. Active microglial engulfment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 106 publications
(135 reference statements)
2
4
1
Order By: Relevance
“…Kruskal-Wallis test followed by Mann-Whitney comparisons; PND14: n-3 deficient-Saline vs n-3 deficient-LPS, ***p < 0.001. PND21: n-3 sufficient-Saline vs n-3 sufficient-LPS, **p = 0.0011, n-3 sufficient-LPS vs n-3 deficient-LPS, ***p = <0.0004. findings reinforce our previous observations that early-life n-3 PUFA dietary deficiency alters post-natal microglia phenotype and phagocytic activity in the hippocampus [44,77,159]. However, while n-3 PUFA deficiency combined with MIA further increased Iba-1/PSD95 colocalization at PND14, at PND28 the spine density in this group was higher compared with that of saline-injected n-3 deficient mice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Kruskal-Wallis test followed by Mann-Whitney comparisons; PND14: n-3 deficient-Saline vs n-3 deficient-LPS, ***p < 0.001. PND21: n-3 sufficient-Saline vs n-3 sufficient-LPS, **p = 0.0011, n-3 sufficient-LPS vs n-3 deficient-LPS, ***p = <0.0004. findings reinforce our previous observations that early-life n-3 PUFA dietary deficiency alters post-natal microglia phenotype and phagocytic activity in the hippocampus [44,77,159]. However, while n-3 PUFA deficiency combined with MIA further increased Iba-1/PSD95 colocalization at PND14, at PND28 the spine density in this group was higher compared with that of saline-injected n-3 deficient mice.…”
Section: Discussionsupporting
confidence: 90%
“…In normal conditions, microglia guide axons, phagocyte apoptotic neurons, refine spines and synapses, in an activity-dependent manner [29,30,[32][33][34][35][36][37][38][39][40][41][42][43]. Both MIA and nutritional imbalance have been shown to disrupt these processes, which might explain the long-term structural and behavioral defects [8,9,16,44]. Myelination is also sensitive to early-life insults and a decrease in white matter integrity is a marker of most, if not all, NDDs [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…These changes in gene expression seem to occur differently between ages, sexes, and brain regions. Similarly, upon exposure to a maternal low n -3 PUFA diet, offspring’s brain transcriptomic signature revealed increased expression of transcript cluster associated to innate immune response and inflammation in n -3 PUFA-deficient mice ( Madore et al, 2019 ). Moreover, both mHFD and maternal low n -3 PUFA studies reported changes in microglial density, morphology, mRNA/protein expression, or functions associated with brain development alterations, commonly observed in neuropsychiatric disorders ( Bilbo and Tsang, 2010 ; Rey et al, 2018 ; Madore et al, 2019 ; Bordeleau et al, 2020 ).…”
Section: Implication For Pregnancy and The Progenymentioning
confidence: 99%
“…Similarly, upon exposure to a maternal low n -3 PUFA diet, offspring’s brain transcriptomic signature revealed increased expression of transcript cluster associated to innate immune response and inflammation in n -3 PUFA-deficient mice ( Madore et al, 2019 ). Moreover, both mHFD and maternal low n -3 PUFA studies reported changes in microglial density, morphology, mRNA/protein expression, or functions associated with brain development alterations, commonly observed in neuropsychiatric disorders ( Bilbo and Tsang, 2010 ; Rey et al, 2018 ; Madore et al, 2019 ; Bordeleau et al, 2020 ). Although the impact of maternal nutrients other than fats and sugar has not been studied yet in the context of neuroinflammation changes in the offspring, it should be expected that their inflammatory effects in the mother have a ripple effect in the brain of the offspring, contributing to neurodevelopmental alterations.…”
Section: Implication For Pregnancy and The Progenymentioning
confidence: 99%
“…In rodents, perinatal dietary n-3 PUFA deficiency decreases brain DHA and concomitantly reduces neurogenesis, synaptic plasticity and connectivity (38)(39)(40)(41)(42) . Perinatal dietary n-3 PUFA deficiency impairs synaptic pruning, the selective phagocytosis of spines by microglia during brain development (43) , in the visual system and the hippocampus (44,45) . The mechanisms underlying the crucial role of DHA in brain development and neuronal network formation is still poorly understood.…”
Section: The Role Of Pufa In Synapse Formationmentioning
confidence: 99%